The role of wrist anthropometric measurement in idiopathic carpal tunnel syndrome - Lim, P.G.; Tan, S.; Ahmad, T.S. (Elsevier, 2008)
Anthropometric wrist measurement ratios were examined for an association with idiopathic carpal tunnel syndrome (CTS). Wrist measurements were recorded in 67 patients with CTS and in a matched control group of 67 healthy volunteers. The Wrist Ratio (WR) (wrist anterior to posterior dimension/wrist medial–lateral dimension) and the Wrist Palm Ratio (wrist anterior to posterior dimension/palm length) were calculated for each case. We found that a WR of ≥0.70 and a Wrist Palm Ratio of >0.342 were significantly associated with idiopathic CTS.